Feeding and contaminant patterns of sub-arctic and arctic ringed seals: Potential insight into climate change-contaminant interactions. (15th November 2022) - Facciola, Nadia; Houde, Magali; Muir, Derek C.G.; Ferguson, Steven H.; McKinney, Melissa A.
Abstract: To provide insight into how climate-driven diet shifts may impact contaminant exposures of Arctic species, we compared feeding ecology and contaminant concentrations in ringed seals ( Pusa hispida ) from two Canadian sub-Arctic (Nain at 56.5°N, Arviat at 61.1°N) and two Arctic sites (Sachs Harbour at 72.0 °N, Resolute Bay at 74.7 °N). In the sub-Arctic, empirical evidence of changing prey fish communities has been documented, while less community change has been reported in the Arctic to date, suggesting current sub-Arctic conditions may be a harbinger of future Arctic conditions. Here, Indigenous partners collected tissues from subsistence-harvested ringed seals in 2018. Blubber fatty acids (FAs) and muscle stable isotopes (δ 15 N, δ 13 C) indicated dietary patterns, while measured contaminants included heavy metals (e.g., total mercury (THg)), legacy persistent organic pollutants (e.g., dichlorodiphenyltrichloroethanes (DDTs)), polybrominated diphenyl ethers (PBDEs), and per-/polyfluoroalkyl substances (PFASs). FA signatures are distinct between sub-Arctic and Resolute Bay seals, likely related to higher consumption of southern prey species including capelin ( Mallotus villosus ) in the sub-Arctic but on-going feeding on Arctic species in Resolute Bay. Sachs Harbour ringed seals show FA overlap with all locations, possibly consuming both southern and endemic Arctic species. Negative δ 13 C estimates for PFAS models suggest that more pelagic, sub-Arctic type prey (e.g., capelin) increases PFAS concentrations, whereas the reverse occurs for, e.g., THg, ΣPBDE, and ΣDDT. Inconsistent directionality of δ 15 N estimates in the models likely reflects baseline isotopic variation not trophic position differences. Adjusting for the influence of diet suggests that if Arctic ringed seal diets become more like sub-Arctic seals due to climate change, diet-driven increases may occur for newer contaminants like PFASs, but not for more legacy contaminants. Nonetheless, temporal trends studies are still needed, as are investigations into the potential confounding influence of baseline isotope variation in spatial studies of contaminants in Arctic biota. Graphical abstract: Image 1 Highlights: Fatty acids and stable isotopes used as diet tracers for ringed seals at four sites. Diet tracers differ between ringed seals of the sub-Arctic and Arctic. Stable isotopes best explain contaminant variation among ringed seals. Diet differences linked to higher levels of PFASs in sub-Arctic seals. Future climate-driven diet shifts in Arctic seals may increase levels of new POPs.